A CHAPTER REVIEW: WRITING MATERIAL FOR ESOL (ENGLISH FOR SPEAKERS OF OTHER LANGUAGES): (The Routledge Handbook of Materials Development for Language Teaching-Routledge) - Mustaqimah Muh Tang; Muhajirah Idman; Andi Tarbiyah Hasan (Al-Irsyad: Journal of Education Science, 2023)
This article's objective is to review Chapter 23 of Naeema B.Hann’s script in book "the Routledge of materials Development for Language Teaching-Routledge," which was edited and compiled in 2022 by Julie Norton and Heather Buchanandi. Starting with the development of ESOL, this is nearly identical to teaching ESL and only differs in terms of the students’ home countries and languages. The author raises the issue of how adults learn the language they need, the context of language use and ESOL learning and the approaches used in teaching language in ESOL classes. Reviewer notes various benefits in this work, including the fact that the author of this chapter goes into great detail to describe the origins of ESOL in the context of teaching English. This development ultimately generated a discussion about how teachers might create pedagogical materials that cater to students' needs so that these resources can be effective in students' lives both in the workplace and in social settings.